MENINGKATKAN STRATEGI PEMASARAN PADA USAHA KOPI - Rodhiah; Sari, Iis Nuraisah Fatmala; Syahri, Anggun Aisyah (Transpublika Publisher, 2022)
The main competition from business people besides product quality issues is a matter of marketing strategy. The marketing strategy carried out by competitors for packaged coffee products is totality, massive, and very brave in terms of spending promotional resources, so companies really need to adjust marketing competition so that the product is not left behind and continues to exist. The activity partners are engaged in the coffee business with the sweet fragrant brand. In his activities facing problems, especially in terms of knowledge about marketing strategies. For this reason, this community service activities aim to assist partners in an effort to increase their knowledge of marketing strategies. The method offered in this activity is training/socialization by coming directly to the partner's location. Marketing strategy material includes: elements in the marketing mix, market segmentation strategy, setting market targets, differentiation and positioning. This activity includes various forms of strategy that must be carried out in serving consumers. The results of the activities carried out run smoothly, partners get stock of knowledge about marketing strategies, in the efforts of partners to face competitive conditions and maintain existing markets and add new ones.